History of the Evolution of Muslim Personal Law in India - Rahiman, K K Abdul (Journal of Dharma, 1986)
The demand for a Uniform Civil code as contemplated in Article 44 of the Constitution of India has gained momentum in recent times. It has also provoked intense opposition from a section of the Muslim community. As this is a problem affecting the rights and duties of an important community in India and is also likelv to affect communal harmony it is worthwhile to study the gradual stages of the evolution of Muslim personal law in our country and as to how the Islamic legal system has been handled by the successive rulers.